Characterisation and comparative analysis of mitochondrial genomes of false, yellow, black and blushing morels provide insights on their structure and evolution - Gang Tao; Steven Ahrendt; Shingo Miyauchi; XiaoJie Zhu; Hao Peng; Kurt Labutti; Alicia Clum; Richard Hayes; Patrick S. G. Chain; Igor V. Grigoriev; Gregory Bonito; Francis M. Martin (IMA Fungus)
Morchella species have considerable significance in terrestrial ecosystems, exhibiting a range of ecological lifestyles along the saprotrophism-to-symbiosis continuum. However, the mitochondrial genomes of these ascomycetous fungi have not been thoroughly studied, thereby impeding a comprehensive understanding of their genetic makeup and ecological role. In this study, we analysed the mitogenomes of 30 Morchellaceae species, including yellow, black, blushing and false morels. These mitogenomes are either circular or linear DNA molecules with lengths ranging from 217 to 565 kbp and GC content ranging from 38% to 48%. Fifteen core protein-coding genes, 28–37 tRNA genes and 3–8 rRNA genes were identified in these Morchellaceae mitogenomes. The gene order demonstrated a high level of conservation, with the cox1 gene consistently positioned adjacent to the rnS gene and cob gene flanked by apt genes. Some exceptions were observed, such as the rearrangement of atp6 and rps3 in Morchella importuna and the reversed order of atp6 and atp8 in certain morel mitogenomes. However, the arrangement of the tRNA genes remains conserved. We additionally investigated the distribution and phylogeny of homing endonuclease genes (HEGs) of the LAGLIDADG (LAGs) and GIY-YIG (GIYs) families. A total of 925 LAG and GIY sequences were detected, with individual species containing 19–48HEGs. These HEGs were primarily located in the cox1, cob, cox2 and nad5 introns and their presence and distribution displayed significant diversity amongst morel species. These elements significantly contribute to shaping their mitogenome diversity. Overall, this study provides novel insights into the phylogeny and evolution of the Morchellaceae.